Chronic toxicity of double-walled carbon nanotubes to three marine organisms: influence of different dispersion methods. (August 2010) - Kwok, Kevin WH; Leung, Kenneth MY; Flahaut, Emmanuel; Cheng, Jinping; Cheng, Shuk Han
Aim: Double-walled carbon nanotubes (DWNTs) are found in a variety of consumer products, but there are no ecotoxicity data of DWNTs into marine organisms.Materials & methods: Chronic toxicity of DWNTs was investigated with the diatom Thalassiosira pseudonana, copepod Tigriopus japonicus and medaka Oryzias melastigma . DWNTs were dispersed using sonication (so-DWNTs) and stirring (st-DWNTs) for comparison.Results: The median aggregation size (0.89 µm 2 ) of so-DWNTs was smaller than that of st-DWNTs (21.8 µm 2 ). Exposure to DWNTs led to growth inhibition of T. pseudonana with EC50 s of 1.86 and 22.7 mg/l for so- and st-DWNTs, respectively. Population growth of T. japonicus was reduced to 0.1 mg/l for so-DWNTs and 10 mg/l for st-DWNTs. Growth inhibition in O. melastigma was observed at 10 mg/l for so-DWNTs but not for st-DWNTs.Conclusion: Given that so-DWNTs are consistently significantly more toxic than st-DWNTs, dispersion method and size of aggregations should be considered in DWNT toxicity testing.